Immunofluorescence–based biosensor for the determination of dengue virus NS1 in clinical samples - Darwish, Nadiya Taha; Sekaran, Shamala Devi; Alias, Yatimah; Khor, Sook Mei (Elsevier, 2018)
The sharp increase in incidence of dengue infection has necessitated the development of methods for the rapid diagnosis of this deadly disease. Here we report the design and development of a reliable, sensitive, and specific optical immunosensor for the detection of the dengue nonstructural protein 1 (NS1) biomarker in clinical samples obtained during early stages of infection. The present optical NS1 immunosensor comprises a biosensing surface consisting of specific monoclonal NS1 antibody for immunofluorescence-based NS1 antigen determination using fluorescein isothiocyanate (FITC) conjugated to IgG antibody. The linear range of the optical immunosensor was from 15 − 500 ng mL−1, with coefficient of determination (R2) of 0.92, high reproducibility (the relative standard deviation obtained was 2%), good stability for 21 days at 4 °C, and low detection limit (LOD) at 15 ng mL−1. Furthermore, the optical immunosensor was capable of detecting NS1 analytes in plasma specimens from patients infected with the dengue virus, with low cross − reaction with plasma specimens containing the Japanese encephalitis virus (JEV) and Zika virus. No studies have been performed on the reproducibility and cross-reactivity regarding NS1 specificity, which is thus a limitation for optical NS1 immunosensors. In contrast, the present study addressed these limitations carefully where these two important experiments were conducted to showcase the robustness of our newly developed optical-based fluorescence immunosensor, which can be practically used for direct NS1 determination in any untreated clinical sample.